2020
DOI: 10.1002/anie.201914752
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Carbide‐Oxide Heterostructures: In Situ Surface Reconfiguration toward Efficient Electrocatalytic Hydrogen Evolution

Abstract: Heterostructured Mo2C‐MoOx on carbon cloth (Mo2C‐MoOx/CC), as a model of easily oxidized electrocatalysts under ambient conditions, is investigated to uncover surface reconfiguration during the hydrogen evolution reaction (HER). Raman spectroscopy combined with electrochemical tests demonstrates that the MoVI oxides on the surface are in situ reduced to MoIV, accomplishing promoted HER in acidic condition. As indicated by density functional theoretical calculations, the in situ reduced surface with terminal Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(100 citation statements)
references
References 52 publications
2
95
0
3
Order By: Relevance
“…However, the surface metal atoms of Mo 2 C and other carbide catalysts are easily oxidized in aerobic environments, creating a thin adherent surface oxide layer. 22,23,[27][28][29] In previous reports, the existence of Mo in low and high valence states is commonly observed in Mo 2 C nanomaterials, with Mo 2+ , Mo 4+ and Mo 6+ frequently being seen by XPS. 15,23,[30][31][32][33] The 4+ and 6+ oxidation states generally result from surface oxidation of Mo 2 C, with their role in the HER over Mo 2 C-based catalysts having received little attention to date.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the surface metal atoms of Mo 2 C and other carbide catalysts are easily oxidized in aerobic environments, creating a thin adherent surface oxide layer. 22,23,[27][28][29] In previous reports, the existence of Mo in low and high valence states is commonly observed in Mo 2 C nanomaterials, with Mo 2+ , Mo 4+ and Mo 6+ frequently being seen by XPS. 15,23,[30][31][32][33] The 4+ and 6+ oxidation states generally result from surface oxidation of Mo 2 C, with their role in the HER over Mo 2 C-based catalysts having received little attention to date.…”
Section: Introductionmentioning
confidence: 91%
“…It was found that the HER activity of Mo 2 C materials can be signicantly improved by fabrication of Mo 2 Cbased heterostructures such as Mo 2 N-Mo 2 C, 14,15 MoC-Mo 2 C, 16 Ni/Mo 2 C-PC, 17 NiMo 2 C/NF, 18 Mo x C/Ni, 19 nw-W 4 Mo, 20 and others. [21][22][23][24][25][26] The high activity of these heterostructures derives from synergistic electron transfer and mass transfer phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Note that, the i-t curve of NiFe 2 O 4 / Ni 3 S 4 is not smooth because of O 2 bubble formation and release from the electrode. [42] Such robust stability of NiFe 2 O 4 /Ni 3 S 4 was further confirmed in the accelerated durability test (ADT) by comparing the overpotential increase at a certain current density after 5000 cycles of potential scans. Specifically, at the current density of 20 mA cm À 2 , after 5000 cycles, extra 32 mV of overpotential increased (Figure 3e), while in sharp comparison, the IrO 2 catalyst required an additional overpotential of 54 mV (Figure 3f).…”
Section: Resultsmentioning
confidence: 76%
“…Meanwhile, heterostructures with abundant interface or element doping also improve the catalytic activity through the modified electronic state [31][32][33][34][35][36]. For example, He et al [37] designed Mo 2 C-MoO x on carbon cloth in which the carbon cloth provided high conductivity and Mo 2 C-MoO x heterojunction improved the catalytic activity, resulting in enhanced HER performance compared with the single phase counterparts. However, the crystals that grow on the surface of carbon cloth tend to fall off during long-time reaction, resulting in instability.…”
Section: M-h Ad + 2ohmentioning
confidence: 99%
“…3h) confirms that two sides of the interface are the fringes corresponding to the (101) plane of Mo 2 C and the (112) plane of Mo 2 N, respectively. The interface always induces the optimization of electronic configuration and adsorption free energy through the interfacial electron transfer through heterointerfaces, achieving synergistic effect to improve electrocatalytic activity [13,37]. Fig.…”
Section: Science China Materialsmentioning
confidence: 99%